Hydroxyl radicals' production and ECG parameters during ischemia and reperfusion in rat, guinea pig and rabbit isolated heart - Paulova, Hana; Stracina, Tibor; Jarkovsky, Jiri; Novakova, Marie; Taborska, Eva (General physiology and biophysics, 2013)
Ischemic and reperfusion injury is a serious condition related to numerous biochemical and electrical abnormalities of the myocardium. It has been repeatedly studied in various animal models. In this study, the production of hydroxyl radicals and electrophysiological parameters were compared in three species. Rat, guinea pig and rabbit isolated hearts were perfused according to Langendorff under strictly identical conditions. The heart rate and arrhythmia were monitored during ischemia and reperfusion periods at defined time intervals; the production of hydroxyl radical was determined by HPLC as 2.5-dihydroxybenzoic acid (2.5-DHBA) formed by salicylic acid hydroxylation. Relationship between arrhythmias and production of 2.5-DHBA was studied. The inter-species differences were observed in timing of arrhythmias onset and their severity, and in the production of 2.5-DHBA in both ischemia and reperfusion. The most considerable changes were observed in rats, where arrhythmias appeared early and with highest severity during ischemia on one side and the regular rhythm was restored early and completely during reperfusion. The corresponding changes in the production of 2.5-DHBA were observed. It can be concluded that rat isolated heart is the most suitable model for evaluation of ischemia/reperfusion injury under given experimental conditions.
Keywords: elektrokardiografie; Rats; srdeční arytmie; Guinea Pigs; gentisáty; Hydroxyl Radical; mužské pohlaví; hydroxylový radikál; Myocardial Reperfusion Injury; Rats, Wistar; Arrhythmias, Cardiac; Heart Rate; krysa rodu Rattus; morčata; srdeční frekvence; reperfuzní poškození myokardu; Electrocardiography; ženské pohlaví; zvířata; Humans; králíci; Rabbits; Gentisates; potkani Wistar; Female; lidé; Male; Animals